Music cultures in the United States : an introduction - Koskoff, Ellen, 1943- (Routledge, 2005)
The first major textbook to explore US music cultures, it takes a new look at the subject by focussing on cultural-historical issues. Expert writers and pedagogic material ensure the most knowledgeable account of America's musical identity.